Current Approaches of Salivary Glands Regeneration for Management of Xerostomia and Hyposalivation: A Narrative Review - Mahdani, Fatma Yasmin; Ayuningtyas, Nurina Febriyanti (Indonesian Journal of Dental Medicine, 2023)
Background: The salivary glands are the organs that produce saliva and have a role keeping the oral cavity moist and lubricated. Salivary glands regeneration is important for developing treatments on management of xerostomia and hyposalivation because of the irreversible damage of salivary glands. Common causes include aging, polypharmacy, autoimmune disease, including Sjogren's syndrome, and head and neck radiation, in which xerostomia and hyposalivation having a substantial impact on patient health and wellbeing. Purpose: to describe current approach of salivary glands regeneration for management of xerostomia and hyposalivation through narrative review. Review(s): A literature search using Science Direct and PubMed yielded results between 1973 and 2022, and the results were evaluated to identify the most promising approaches and for future research. The keywords of the search strategy were "salivary gland regeneration” and "xerostomia” or "hyposalivation”. Current studies have revealed potential targets in the development of salivary gland regeneration for the management of xerostomia and hyposalivation. Stem cells therapy aims to repair damaged at the cellular level, especially stimulating acini cells, multiplying and differentiating to replace dead or damaged acini cells. Bioengineering is through isolated acini cells cultured on many modified cell line and administration of bioactive compounds. Gene therapy aims to rebuild functional water channels and neutralization of inflammatory mediators. Conclusion: Several approaches of salivary glands regeneration that can be taken are stem cells therapy, bioengineering, and gene transfer.